2009
DOI: 10.1183/09031936.00018709
|View full text |Cite
|
Sign up to set email alerts
|

Cryptogenic haemoptysis in smokers: angiography and results of embolisation in 35 patients

Abstract: The aim of the present study was to describe angiographic findings and embolisation results in smokers with haemoptysis.We retrospectively reviewed the clinical data and angiographic findings from 35 patients with smoking-related bronchopulmonary disease and no associated comorbidity, who were referred for embolisation for mild (n56), moderate (n514) and severe (n515) haemoptysis. Spirometric classification subdivided our population into: 16 patients with chronic bronchitis but no airflow limitation; and 19 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
1
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 33 publications
(41 reference statements)
3
23
1
6
Order By: Relevance
“…If bronchoscopy reveals the lesion, artery embolization should be the next step followed by surgery, if required. If bronchoscopy does not reveal any abnormality, a cryptogenic massive hemoptysis is diagnosed and embolization may be indicated, particularly in smokers (17).…”
Section: Massive Hemoptysismentioning
confidence: 99%
See 2 more Smart Citations
“…If bronchoscopy reveals the lesion, artery embolization should be the next step followed by surgery, if required. If bronchoscopy does not reveal any abnormality, a cryptogenic massive hemoptysis is diagnosed and embolization may be indicated, particularly in smokers (17).…”
Section: Massive Hemoptysismentioning
confidence: 99%
“…According to different authors, etiology of hemoptysis cannot be determined in 3% to 42% of cases and it is defined as cryptogenic (7,16,17). Nevertheless, it has been demonstrated that a proportion of patients presenting with hemoptysis without any morbidity are smokers, and bleeding in smokers should be defined as smoke-related (occurring as a result of tobacco-induced bronchial wall inflammation), rather than cryptogenic (17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bronşiektazi, kronik bronşit, tüberküloz, mikotik akciğer enfeksiyonları, akciğer apsesi, kronik inflamatuar hastalıklar ile birlikte neoplastik hastalıklar anjiogenik büyüme faktörlerin salgılanmasını sağlayarak pulmoner damar neovasküla-rizasyona neden olurlar. Bu yeni kollateral damarlar frajildir ve hava yolu içine kanama eğilimindedirler (19)(20)(21).…”
Section: Akci̇ğeri̇n Arteryel Anatomi̇si̇ Ve Hemopti̇zi̇ni̇n Patofi̇zyoloji̇k unclassified
“…In our study we considered following classification system; <100 cc/day of hemoptysis as mild, 100-150 cc/day as moderate, 150-200 cc/day as severe, and >500 cc/day of expectorated blood in 24 hours or rate of blood loss >150ml/hr or 200ml blood loss/day for more than 3 days as massive hemoptysis. [3][4][5][6] The source of bleeding is usually from erosion of systemic rather than pulmonary arteries. Notable exceptions are arterio-venous malformations and pulmonary artery aneurysms.…”
Section: Introductionmentioning
confidence: 99%